Judas horse - La Plante, Lynda (La Plante, Lynda. DC Jack Warr, 2021)
"When Detective Jack Warr identifies an informer, the terrified man begins to give details of a massive robbery planned by a team of unscrupulous and dangerous men. These men have already orchestrated many audacious robberies, leaving terrified victims in their wake. And they have already killed to get what they want. Detective Jack Warr and his team must use their informant as a 'Judas Horse' to draw in the unsuspecting robbers, so that they go ahead with the planned robbery. However, one false move, and more blood will be spilled"--